ANALISIS PENGARUH KOMPETENSI SDM DAN PERAN AUDIT INTERNAL TERHADAP KUALITAS LK SKPD DENGAN SPIP SEBAGAI VARIABEL INTERVENING STUDI EMPIRIS SEKRETARIAT DAERAH KABUPATEN/KOTA SE-JAWA TENGAH - Nisa, Luthfi Khoirun; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2021)
This research was conducted to analyze the influence of HR competence (Human Resources) and the role of internal audit on the quality of LK SKPD (Regional Work Unit Financial Statements) with SPIP (Government Internal Control System) as an intervening variable. The variables used are HR competency and the role of internal audit as an independent variable, LK SKPD quality as the dependent variable and SPIP as an intervening variable. The sample in this study were financial employees of the Regional Secretariats of Regency/City in Central Java. The sample based on purposive sampling method. The sample obtained was 35 respondents. The research method used is hypothesis testing research by using PLS (Partial Least Square) test tool.The results showed that HR competency and the role of internal audit had a positive but insignificant effect on the quality of LK SKPD and the role of internal audit also had a positive but insignificant effect on SPIP and the role of internal audit had a positive and insignificant effect on the quality of LK SKPD mediated by SPIP. However, SPIP affects LK SKPD positively and significantly, HR competencies affect SPIP positively and significantly and HR competencies affect the quality of LK SKPD mediated by SPIP positively and significantly.